2015
DOI: 10.1615/critrevoncog.v20.i5-6.100
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-β and the Insulin-Like Growth Factor Axis as Potential Therapeutic Targets for Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancers (TNBCs) lack estrogen receptor-α (ERα), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER2) amplification and account for almost half of all breast cancer deaths. This breast cancer subtype largely affects women who are premenopausal, African-American, or have BRCA1/2 mutations. Women with TNBC are plagued with higher rates of distant metastasis that significantly diminish their overall survival and quality of life. Due to their poor response to chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 149 publications
(219 reference statements)
0
9
0
Order By: Relevance
“…In the case of BPA, it has been reported that under in vivo conditions, BPA is readily converted to BPA-glucuronide (via phase II reaction); however, BPAglucuronide has itself also been proven to be a possible active metabolite that induces adipogenesis in human and murine preadipocytes (Boucher et al, 2015). Although it has been suggested that ERb has a possible protective role against breast tumor progression, the accumulated evidence suggests that ERb also acts as a mediator of estrogen action, coupled with tumorigenesis, in breast cancer cells, and that its expression is remarkably upregulated in tamoxifen-resistant breast cancers (Dotzlaw et al, 1999;Speirs et al, 1999a,b;Power and Thompson, 2003;Hamilton et al, 2015;Ma et al, 2017). Collectively, including our findings here, it is suggested that the negative biologic effects of BPA are exerted through several Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of BPA, it has been reported that under in vivo conditions, BPA is readily converted to BPA-glucuronide (via phase II reaction); however, BPAglucuronide has itself also been proven to be a possible active metabolite that induces adipogenesis in human and murine preadipocytes (Boucher et al, 2015). Although it has been suggested that ERb has a possible protective role against breast tumor progression, the accumulated evidence suggests that ERb also acts as a mediator of estrogen action, coupled with tumorigenesis, in breast cancer cells, and that its expression is remarkably upregulated in tamoxifen-resistant breast cancers (Dotzlaw et al, 1999;Speirs et al, 1999a,b;Power and Thompson, 2003;Hamilton et al, 2015;Ma et al, 2017). Collectively, including our findings here, it is suggested that the negative biologic effects of BPA are exerted through several Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that ERb may be a tumor suppressor owing to its reduced expression during cancer development (Iwao et al, 2000). However, the accumulated evidence suggests that ERb also acts as a mediator of estrogen action in breast cancer cells (Speirs et al, 1999a;Hamilton et al, 2015;Ma et al, 2017). Thus, in the present study, we investigated the effects of repeated exposure to BPA, together with MBP, at concentrations similar to environmental levels on the expression of ERa/b, and investigated the ER subtype that was involved in these effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, conformation of E2 binding of plasma membrane proteins was established through ERα knockout models in astrocytes [69]. Although ERs localize predominantly in tumor cell nuclei, a significant pool of ERs has been shown to localize in extranuclear sites in archival BC and NSCLC cells [41, 66, 70, 71]. Thus, important actions initiated by membrane-associated forms of ER may play a collaborative role with liganded-ERs in the nucleus to promote signaling for hormone-mediated proliferation and survival of BCs.…”
Section: Introductionmentioning
confidence: 99%
“…ERβ forms occur in tumor cell nuclei, but also at extranuclear sites [71, 264]. ERβ can activate transcription by nuclear or indirectly by extranuclear pathways by interaction with coactivators/co-regulators such as PELP1 and SRAP [265] that in turn modulate signaling cascades to impact gene expression and TNBC progression [70, 71, 264, 266, 267]. As a consequence of such preclinical work, clinical studies to target ERβ are being planned in patients afflicted with metastatic TNBC [268].…”
Section: Introductionmentioning
confidence: 99%
“…Products of primary responsive genes further promote the transcription of secondary or tertiary responsive genes, finally resulting in a dynamic action. These signal pathways crosstalk with the other signal transduction pathways through growth factor receptors or various membrane-bound receptors ( Figure 3 ) [ 12 , 63 , 64 ].…”
Section: Sex Steroid Hormone Receptors Other Than Er-α and Pgrmentioning
confidence: 99%